Analysis of the Function and Convenience of Pedestrian Public Transport Support the City of Bogor - Syaiful, Syaiful; Yulianto, Muhammad; Murtejo, Tedy; Rulhendri, Rulhendri (Universitas Ibn Khaldun Bogor, 2023)
By looking at the conditions of the pedestrian paths located on the road section of Rd. KH. Sholeh Iskandar, the center point is at the Uika bus stop and the drug monument stop 2, as well as Rd. KH. R. Abdullah bin nuh, the center point is at the Bubulak terminal, Yasmin shop shelter and Bogor radar shelter. the author analyzes the pedestrian path as a supporting access for public transport users. The research objectives to be achieved, among others, are to analyze existing conditions, calculate the level of pedestrian service, and analyze the perceptions of pedestrian lane users. In this study, researchers analyzed the level of pedestrian service referring to the technical planning guidelines, 1991 and produced the Level of service (LOS) for the performance of pedestrian facilities.